Implementasi Pembelajaran PJOK pada Masa Pandemi Covid-19 di SMP Sederajat Se-Kecamatan Ajibarang - Munir Al Fadhil; Ranu Baskoro Aji Putra (Universitas Negeri Semarang, 2022)
COVID-19 in various countries including Indonesia has an impact on various fields of education. Teachers have limited time, many students do not have mobile phones, and the signal or internet connection is unstable. This condition raises various problems related to factors that affect the achievement of learning objectives. This study uses qualitative research with a descriptive approach, with data sources taken from 6 principals, 12 teachers and 30 students taken from 5 students from each school as a sample. In this study using a descriptive approach, where this descriptive study aims to provide an overview and understanding of the phenomena experienced by the object. The results of this research are planning is carried out with distance learning lesson plans, preparing learning media with video content, the implementation of PJOK learning is carried out online throughout schools using student worksheets (LK) and online through the school's website, whatsapp grub, and google classroom, and the assessment or evaluation is carried out through three aspects, namely affective, cognitive, and psychomotor aspects. The conclusion in this study is that PJOK learning during the Covid-19 pandemic at the equivalent junior high school in Ajibarang District, Banyumas Regency was less effective.